What drives the [CII]/FIR deficit in submillimeter galaxies?. Issue Volume 15:Issue S352(2019) (June 2019) - Rybak, Matus; Hodge, J. A.; Calistro Rivera, G.
Abstract: Submillimeter galaxies at redshift z ⩾1 show a pronounced [CII]/FIR deficit down to sub-kpc scales; however, the physical origin of this deficit remains poorly understood. We use resolved ALMA observations of the [CII], FIR and CO(3–2) emission in two z = 3 SMGs to distinguish between the different proposed scenarios; the thermal saturation of the [CII] emission is the most likely explanation.